2015
DOI: 10.4236/me.2015.63030
|View full text |Cite
|
Sign up to set email alerts
|

Trade Liberalization and Disaggregated Import Demand in Uganda

Abstract: Studies investigating determinants of import demand for Uganda present aggregate findings yet there is a need to disaggregate the findings for specific sectors. This creates a research gap on disaggregated findings of import demand. This research attempts to fill this research gap by establishing determinants of import demand using disaggregated sector level data for consumer, intermediate and capital goods. The study estimates the long-run and short-run import demand elasticities for consumer, intermediate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
5
1
Order By: Relevance
“…However, it is recommended that, to address the negative impact of investment spending on capital good, the government should design fiscal policies in a manner that encourages import substitution, boosts domestic production capacity, and discourages consumption-oriented imports. The negative effect of trade policy is inconsistent with theory; however, it is supported by findings in previous studies, such as Narayan and Narayan (2005) and Samuel (2015).…”
Section: Short-run and Long-run Resultscontrasting
confidence: 59%
“…However, it is recommended that, to address the negative impact of investment spending on capital good, the government should design fiscal policies in a manner that encourages import substitution, boosts domestic production capacity, and discourages consumption-oriented imports. The negative effect of trade policy is inconsistent with theory; however, it is supported by findings in previous studies, such as Narayan and Narayan (2005) and Samuel (2015).…”
Section: Short-run and Long-run Resultscontrasting
confidence: 59%
“…Domestically, NERICA yields at farmer fields is found to be 56 percent of that at the station (2.2 tones per hectare as opposed to 5 tonnes per hectare envisaged by WARDA [9] The production estimates provided by UBOS [6] were even lower; estimated at 1.36 per hectare. Yet, [10] results showed that rice farmers growing irrigated rice were not reaching their potential mainly due to limited access to extension services and credit.…”
Section: Introductionmentioning
confidence: 82%
“…Since the crop is that important, especially in urban areas especially among the youth, and government institutions in the country a strategy plan was drawn up in 2009 to redirect the farmer's efforts to benefit consumers as well as the nation at large. Prior to the formulation of this strategy, a number of studies carried out in the country established that the crop competed well within the farming system [8] [5]; had higher yields than those in Asia Kijima et al, [9]; was profitable [10]) and was facing increasing demand due to changes in tastes, especially in urban areas [11]. However, increases in domestic production is currently faced by many constraints among which are post harvesting practices leading to physical losses and poor milling facilities [12] and many more constraints highlighted in [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter category of studies is usually based in countries whereby imports are dominated by intermediate and capital goods required for economic development. Uganda is an example from Africa in which aggregate imports primarily consist of capital and intermediate goods that mainly serve in production for export purposes (Samuel, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%